Influence of Lumbar Spine Pathology on the Incidence of Paresthesia During Spinal Anesthesia. Issue 6 (November 1998) - Tetzlaff, John E.; Dilger, John A.; Wu, Carleton; Smith, Michael P.; Bell, Gordon
Abstract : Background and Objectives: Paresthesia occasionally occurs during dural puncture or injection of local anesthetic for spinal anesthesia. Although the incidence of neurologic complications after spinal anesthesia is extremely low, the significance of paresthesia is unknown. The influence of known lumbar spine pathology on the incidence of paresthesia during spinal anesthesia is studied. Methods: Incidence of paresthesia with dural puncture (PP) or injection (PI) was studied in two groups of patients. Group 1 included patients for elective total joint replacement without known spine pathology or complaints. Group 2 included patients for elective lumbar spine surgery who received spinal anesthesia. Results: Significantly more PP (20% vs 9%) and PI (16% vs 6%) occurred in the spine surgery group. There were no neurologic sequelae of spinal anesthesia. Conclusions: This information suggests that the incidence of paresthesia during the conduct of spinal anesthesia is higher in patients with lumbar spine pathology. Although there were no neurologic complications, the sample size is too small to exclude an increase in the neurologic risk of spinal anesthesia in patients with known intraspinal pathology.